Knockout of MULTI-DRUG RESISTANT PROTEIN 5 Genes Lead to Low Phytic Acid Contents in Oilseed Rape - Sashidhar, Niharika; Harloff, Hans J.; Jung, Christian (Frontiers in Plant Science, 2020)
Understanding phosphate uptake and storage is interesting to optimize the plant performance to phosphorus fluctuations. Phytic acid (PA) is the major source of inorganic phosphorus (Pi) in plants. Genetic analyses of PA pathway transporter genes (BnMRP5) and their functional characterization might provide clues in better utilizing the available phosphate resources. Furthermore, the failure to assimilate PA by monogastric animals results in its excess accumulation in manure, which ultimately causes groundwater eutrophication. As a first step towards breeding low PA mutants in oilseed rape (Brassica napus L.), we identified knockout mutants in PA biosynthesis and transporter genes. The obtained M3 single mutations of Bn.MRP5.A10 and Bn.MRP5.C09 were combined by crossing to produce double mutants. Simultaneously, crosses were performed with the non-mutagenized EMS donor genotype to reduce the background mutation load. Double mutants identified from the F2 progeny of direct M3 crosses and BC1 plants showed 15% reduction in PA contents with no significant differences in Pi. We are discussing the function of BnMRP5 paralogs and the benefits for breeding Bnmrp5 mutants in respect to low PA, yield and stress tolerances.